Pengaruh Puasa terhadap Jumlah dan Morfologi Spermatozoa Mencit (Mus musculus) - Nurul Marfu'ah; Surya Amal (University Of Darussalam Gontor, 2018)
One of the benefits of fasting is being able to control testosterone levels in the blood so as not to exceed normal. Normal testosterone levels will produce good quality (morphology, viability, motility) and good quantity (number) of spermatozoa. Therefore, this study was conducted to understand the effect of fasting on the number and morphology of spermatozoa in mice. This study is an experimental study with a completely randomized design trial (CRD) using 5 treatments and 3 replications. The type of treatment given is not fasting (control); middle fasting month of Hijriah for 3 days (13th, 14th and 15th); Monday and Thursday fasting; fasting Daud (a day of fasting a day is not); and fasting every day for 36 days. Male mice used in this study were Balb C strains with an initial weight of 23-26 grams and in the age range of 8-10 weeks. Calculation of the number of epididymal spermatozoa carried out according to WHO procedures in Syamrizal (1995) and morphological observations of spermatozoa carried out included normal and abnormal. Data analysis used is one-way ANOVA with a significance level of 5%. The statistical program used for the analysis was the SPSS 20 program. The results showed that fasting could increase the number and percentage of normal spermatozoa in Balb C strain mice eventhough statistically the increase was not significantly different (sig.> 0.05). Based on the type of fasting that was done, fasting on Thursday Thursday had the highest effect on the increase in the number and percentage of normal spermatozoa. Then followed by fasting every day and fasting of Daud. While the mid-fasting month of Hijriah actually decreases the number and percentage of normal spermatozoa compared to controls.